SOME FINE WARES FROM THE EASTERN MEDITERRANEAN IN AQUILEIA BETWEEN THE 2ND AND THE 3RD CENTURY AD - Mandruzzato, Luciana (Rei Cretariae Romanae Fautorum Acta, 2024)
The importance of Aquileia as an emporium with strong relations with the Eastern Mediterranean since the very first years of its foundation as a Roman colony (181 BC) has been increasingly proved by recent investigations on the site.